The role of the writing process in adapting scientific articles in dentistry - Maldonado–Villamizar, Johana (2025)
Writing as the sole tool used by humans is defined as the identification of a set of statements that make complete sense and are linked together to form a communicative text. This text becomes an extension of the discursive, psychological, cultural, and social component of humanity.